Contributions of leaf morphoanatomy to the taxonomy of Bronwenia (Malpighiaceae Juss.) - Pereira Vilarinho, Milena; Da Costa Santos, João Victor; Soares Santos-Filho, Francisco; Silva Araújo, Josiane (Phytotaxa, 2023)
Bronwenia has about 11 species whose current delimitation is the result of a complicated taxonomic history marked by recent evolutionary hypotheses in Malpighiaceae. Therefore, there is a need for approaches that contribute to circumscribing the group and distinguishing the species. Thus, the aim of this work was to prove the effectiveness of leaf anatomy in this purpose and point out the characters that distinguish the species of Bronwenia. Plant anatomy techniques were used and the coded anatomical characters were plotted in a binary matrix and interpreted in a cluster analysis, using UPGMA. The relevant characters to distinguish the taxa were: petiole contour, petiole/midrib vascular system conformation, presence or absence malpighiaceous trichomes and laticifers. While the remaining characters occur widely in the group and can be used in future approaches to distinguish Bronwenia from other related genera, including Diplopterys and Banisteriopsis, which previously constituted a single genus. Therefore, leaf anatomy represents relevance in the taxonomy of Bronwenia and can direct evolutionary hypotheses for Malpighiaceae.